FEMALES IN GOVERNANCE AND CORPORATE TAX AVOIDANCE: THE MODERATING EFFECT OF ACCOUNTING CONSERVATISM (Malaysian Management Journal, 2020)
High cash outflow in the form of corporate taxes reduces the corporate firms’ liquidity, available funds for re-investment and growth opportunities. Corporate firms’ attention is therefore geared towards ensuring minimum tax liability. The purpose of this study is to examine the effect of females’ presence in the governance on corporate tax avoidance, moderating for the role of accounting conservatism. The study is based on the companies listed on the Nigerian Stock Exchange and utilised the ex-post factor research design. The panel corrected standard regressions was employed to test the hypothesis. Female CEO, percentage of female directors and presence of female in the audit committee have significant positive effects on tax avoidance. The moderating for accounting conservatism, the percentage of female directors on the board and female director presence in the audit committee remains significant. The findings may be of interest to the academic researchers, investors and regulators. For academic researchers, it is interested in discovering whether females’ presence in the governance affect tax avoidance and the moderating role accounting conservatism. For investors, it shows that women in the boardroom can improve the bottom line financial performance through tax reduction strategies.This study extends the existing literature by examining the mediating role of accounting conservatism on the relationship between females in governance and tax avoidance in the Nigerian context.